Studying the Relationship between Sports Directors Familiarity with Sports Rights Concepts and Risk Management Behaviors - Cheraghi, Soheila; Veisi, Korosh (Revista Administração em Diálogo - RAD, 2017)
The objective of this research is to investigate the relationship of sports directors’ familiarity with sports rights concepts and risk management behaviors at Kurdistan province in Iran. The methodology of this research is descriptive survey. The research statistical society consisted 255 members of all directors at Kurdistan Sport domain. The sampling method was simple random and for determining the sample volume 150 sport directors’ managers of Kurdistan province, using Morgan table, were selected as the sample. Measuring tool was questionnaires of Thomas Irons about familiarity of managers and directors with sports rights and risk management. Its validity was confirmed by 10 experts and its stability was % 85 and % 89, in order. For theories analysis, Pearson’s correlation coefficient was used. The finding showed that there is relation between the familiarity of sports directors with sports rights concepts, supervision, medical issues, bystander and population control, transportation, safety and applied equipment to their schedule at Kurdistan province. P<0.05; but employment and upbringing, safety, applied equipment and facilities factors do not affect manager’s familiarity with sports rights P>0.05. Finally, it can be said that it seems risk management and sports rights require facilities and specific situations that rarely exist in the country’s organizations and institutions and while it is not the right condition it is not expected these behaviors would happen in a favorable way. The present research concluded valuable results about investigating the relationships of familiarity of sports directors of Kurdistan province, with sports rights concepts and risk management behaviors.